Biomechanical efficiency of different starting techniques in ski cross - Pozzo, R.; Tonon, A.; Canclini, A.; Baroni, G. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
In ski cross the starting phase represents one important influencing factor of the performance. In an investigation on more than 50 Starts during the Olympic Games and at World Cup Competions it was found, that 85% of men and 87% of women athletes who were leading the run at the first turn, reached next qualifications (Argüelles et al., 2011). Specific training devices simulating the typical pull-pushing action of the arms were also developed in order to improve the start performance (Raschner et a l., 2009). Other investigations concerned the influence of pre-activation, the start slope inclination and other aspects (Ebenbichler & Raschner, 2012; Nedergaard et al. 2014, 2015). Basically 3 technique strategies are used: personally free (PF_T); with prevalent arm and shoulder impulse (AS_T horizontal displacement of CoG) and with a full body vertical extension (BE_T) before the hands release. The aim of this study was to investigate the influence of the height of the handles and the use of specific technique strategies, moreover to identify the efficiency of the impulse produced on the handles at the start.